Random Field-Based Time-Dependent Reliability Analyses of a PSC Box-Girder Bridge - Zheheng Chen; Tong Guo; Shaobo Liu; Weiwei Lin (Applied Sciences, 2019)
The parameters affecting structural reliability are usually regarded as independent random variables in the current reliability analyses of bridge structures while the randomness of these structural parameters in spatial distribution is neglected. To overcome this disadvantage, the random field model should be used to describe their probability distribution. In this paper, a structural reliability analysis method considering the effect of a random field is proposed, and its validity is verified by three numerical case studies. A prestressed concrete (PSC) box-girder bridge with a main span of 150 m is selected for demonstration, and the importance sampling (IS) method is applied to estimate its failure probability, in which the influences of shrinkage and creep, stress relaxation, and shear lag on the time-dependent performance of the structure are taken into account. In addition, the random fields of the structure are discretized by using the local average method (LAM). Finally, the effects of random field parameters, such as the number of discrete elements, correlation model, and correlation length, on the reliability of the box-girder bridge are discussed.